Are board characteristics relevant for banking efficiency? Evidence from the US. Issue 4 (1st August 2016) - Titova, Yulia
Abstract : Purpose: This paper examines whether board-related characteristics matter for cost efficiency in banking sector. Design/methodology/approach: We use a sample of publicly traded US commercial banks and savings institutions to estimate a relationship between cost efficiency measured by stochastic frontier analysis (SFA) and a set of board-related characteristics for the period 2007 - 2013. Findings: We find an inverted U-shape relation between board size and efficiency. Thus, there is a trade-off between costs and benefits of larger boards. Optimal board size is higher for banks with more complex operations. We also observe an inverted U-shape relation between board independence and cost efficiency. The banks where the Chairman also executes the CEO responsibility show lower efficiency. However, a higher proportion of independent board members in banks with unitary leadership structure may mitigate the conflict of interest and lower efficiency stemming from the CEO duality. Research limitations/implications: Our evidence supports the Basel Committee on Banking Supervision emphasis on advising a board composition that provides for a sufficient degree of director independence. Practical implications: Our results are relevant for banks and their external and internal stakeholders. Banks may adjust their current board characteristics in order to increase the board effectiveness. Externally, potential investors can evaluate the quality of corporate governance of banks before making investment decisions. Our empirical findings can be also useful for regulators imposing corporate governance codes in banking. Originality/value: To the best of our knowledge, this is the first paper to provide empirical evidence on the impact of board characteristics on bank efficiency for a wide panel of US banks. Additionally, we use a comprehensive set of board-related variables.